Significance of Single-cell Level Dual Expression of BCL2 and MYC Determined With Multiplex Immunohistochemistry in Diffuse Large B-Cell Lymphoma. (3rd March 2022) - Roh, Jin; Yoon, Dok Hyun; Lee, Yoon Kyoung; Pak, Hyo-Kyung; Kim, Sang-Yeob; Han, Jae Ho; Park, Joon Seong; Jeong, Seong Hyun; Choi, Yoon Seok; Cho, Hyungwoo; Suh, Cheolwon; Huh, Jooryung; et al.
Abstract : Diffuse large B-cell lymphoma (DLBCL) is a fatal heterogenous neoplasm. Recent clinical trials have failed partly due to nebulous criteria for defining high-risk patients. Patients with double-expresser lymphoma (DEL) have a poor prognosis and are resistant to conventional treatment. However, many diagnostic and clinical controversies still surround DEL partly due to the arbitrariness of criteria for the diagnosis of DEL. In this study, we suggest a refined method for diagnosing DEL by evaluating the concurrent expression of BCL2 and MYC at the single-cell level (dual-protein–expressing lymphoma [DUEL]). For the proof of concept, a multiplex immunofluorescence assay for CD20, BCL2, and MYC was performed and quantitatively analyzed using spectral image analysis in patients. The analysis results and clinical applicability were verified by using dual-color immunohistochemistry performed on 353 independent multicenter patients who had been uniformly treated with standard therapy. DUEL showed significantly worse overall survival (OS) and event-free survival (EFS) ( P =0.00011 and 0.00035, respectively). DUEL status remained an independent adverse prognostic variable with respect to the International Prognostic Index risk and the cell of origin. Moreover, the advantage of determining DUEL status by dual-color immunohistochemistry was shown by more robust classification and more homogeneous high-risk subgroup patient identification in both training (n=271) (OS: P< 0.0001; EFS: P< 0.0001) and validation sets (n=82) (OS: P =0.0087; EFS: P< 0.0001). This concept of DUEL is more consistent with carcinogenesis and has greater practical utility, hence it may provide a better basis for both basic and clinical research for the development of new therapeutics.